Проблемні аспекти визначення та коригування митної вартості товарів в Україні - Мінакова, Світлана Михайлівна; Запорожець, О. Ф. (Класичний приватний університет, 2019)
У статті розглянуто основні питання визначення та коригування митної вартості товарів в Україні. Значну увагу приділено визначенню сутності дефініцій "митна вартість", "фактурна вартість". Відзначено, що в переважній більшості вчені розглядають митну справу та митний контроль, проте нормативно-правові аспекти цього питання потребують подальшого дослідження. Метою даної статті є аналіз особливостей визначення, контролю та коригування митної вартості товарів в Україні. Проведено аналіз статей 52 та 54 Митного кодексу України з визначенням прав та зобов’язань уповноважених органів та суб’єктів діяльності. Визначено особливості практичної діяльності під час декларування величини митної вартості товарів. Зазначено, що судові справи найчастіше вирішуються на користь суб’єктів зовнішньоекономічної діяльності. Проте в деяких випадках митниці ДФС правомірно приймають рішення щодо коригування митної вартості товарів унаслідок недоотримання підтверджуючих документів. Зазначено основні причини виникнення питань із боку органів доходів і зборів до величини митної вартості.

The article deals with the main issues of definition and adjustment of customs value of goods in Ukraine. Considerable attention is paid to the definition of the essence of the definition of "customs value", "invoice value". It is noted that in the majority of cases, scientists consider and study customs and customs control issues, but the regulatory and legal aspects of this issue requires further research. The objective of the article is to analyze the features of determination, control and adjustment of customs value of goods in Ukraine. The analysis of Articles 52 and 54 of the Customs Code of Ukraine, with the definition of the rights and obligations of authorized bodies and subjects of economic activity is conducted. The peculiarities of practical activity when declaring the value of the customs value of goods are determined. It is noted that litigation is most often solved in favor of entities with foreign economic activity. However, in some cases, the SFS customs authorities make a decision on adjusting the customs value of goods due to lack of supporting documents. These are the main reasons for the emergence of questions from the revenue and fees authorities to the value of customs value. The features of control over the customs value of goods are investigated. It is established that often the decision on the need to submit additional documents for confirming the numerical values of the components of the customs value of goodswas taken on the basis of the operation of the risk management system. In such cases, the automated system of analysis and risk management is in operation. As the analysis of legal and judicial practice shows, as a rule, information on the operation of risk profiles and the difference in the value of the customs value of goods from the one contained in identical or similar goods in the database of the specialized "Price Information" database is not a sufficient evidence base. The latest monitoring of state budget revenues shows that the share of customs payments in the tax revenues is one of the dominant, which, in turn, determines the primary importance of providing SFS customs with precisely the fulfillment of the fiscal function. In order to reach consensus on the definition, control and adjustment of the customs value of goods, it is expedient to ensure the practical implementation of a number of measures to improve the process of determining, controlling and correcting the customs value of goods.
Problems of definition and implementation of customs value of goods in Ukraine
Keywords: Митний кодекс України; економіка; фактурна вартість; customs value of goods; Customs code of Ukraine; invoice value; customs control